Model Pembelajaran Discovery Learning dengan Pendekatan CRT untuk Meningkatkan Kemampuan Berpikir Kritis dan Literasi Membaca - Almahdi, Achmad Arif; Mawardi, Mawardi (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
Preliminary research obtained data that there were fifth grade elementary school students who had levels of critical thinking and reading literacy in the low category. These two abilities are very important for students' academic development, so they need to be improved. The aims of this research are: 1) improve critical thinking skills; 2) improve reading literacy skills; 3) know the value of increasing critical thinking skills, and; 4) know the value of increasing reading literacy skills. The research uses the classroom action research (PTK) method with the Stringer model. The research was carried out over two cycles through 3 stages, namely look, think, and act. The number of samples in cycles I and II was 26 children. Data collection techniques were carried out using tests and non-tests, while the instruments were in the form of questions and questionnaires. The research resulted in: 1) students' critical thinking skills and reading literacy increasing; 2) Critical thinking skills in cycle I had an average of 68 or in the medium category and the average in cycle II was 75 or in the high category; 3) Reading literacy skills in cycles I and II each have an average of 70 in the medium category and 78 in the high category; 4) students' critical thinking skills reach a minimum of 54% in the high category; 4) students' reading literacy skills reach a minimum of 65% in the high category. These data have reached indicators of research success, thus confirming that the discovery learning model with the CRT approach is able to improve critical thinking skills and reading literacy.